2020
DOI: 10.1016/j.jcot.2020.03.007
|View full text |Cite
|
Sign up to set email alerts
|

Tibialis posterior (TP) tendon transfer for foot drop: A single center experience

Abstract: Background: Foot drop defined as a significant weakness of ankle and toe dorsiflexion. It leads to high stepping gait, functional impairment and deformity of the foot. Objective of this study was to assess the functional outcome of tibialis posterior (TP) transfer for patient with foot drop in a single center. Methods: This is a retrospective study included 20 patients operated for foot drop of >1 year duration in the last 5 years. Preoperative assessment of muscles of all the three compartment of leg along wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…Transfer of the tibialis posterior (TP) tendon has been described to stabilize the ankle and statically clear the toes during swing. 17 Although this is generally an improvement, the TP transfer does not restore active dorsiflexion, as the TP naturally performs an antagonistic function. Therefore, our preference is to combine a tendon transfer of the lateral head of gastrocnemius into the TA with simultaneous transfer of its nerve into the proximal peroneal nerve (Table 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…Transfer of the tibialis posterior (TP) tendon has been described to stabilize the ankle and statically clear the toes during swing. 17 Although this is generally an improvement, the TP transfer does not restore active dorsiflexion, as the TP naturally performs an antagonistic function. Therefore, our preference is to combine a tendon transfer of the lateral head of gastrocnemius into the TA with simultaneous transfer of its nerve into the proximal peroneal nerve (Table 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…To showcase the importance of foot and ankle disorders, we have included several high-quality reviews and original research articles, annotations, along with some very interesting case reports and technical tips. The variety of publications, in this special issue, range from fractures, 4,5 arthritis, 6 diabetic foot problems, 7,8 tendon transfer for the foot drop, 9 hallux valgus, club foot and Morton's neuroma. There are also articles on ultrasound-guided regional anaesthesia in foot and ankle surgery and on postoperative rehabilitation.…”
mentioning
confidence: 99%
“…Our outcomes were comparable to the study by Yeap et al, 6 who reported 10 of 12 patients no longer required the use of an orthosis following PT tendon transfer for drop foot. Agarwal et al 20 published similar results and reported that all of their patients, except for one, were able to walk with heel-toe gait without any orthotic support postoperatively.…”
Section: Discussionmentioning
confidence: 66%